Cerium(III) N, N-dibutylcarbamate as precursor to nanocrystalline cerium dioxide. (15th October 2015) - Belli Dell'Amico, Daniela; De Sanctis, Massimo; Ishak, Randa; Dolci, Sara; Labella, Luca; Lezzerini, Marco; Marchetti, Fabio
Graphical abstract: Nanostructured ceria has been prepared in mild conditions by hydrolysis of the N, N -dibutylcarbamato complex of cerium(III), [Ce(O2 CNBu2 )3 ], obtained by lanthanide extraction from aqueous solution into heptane containing CO2 saturated NHBu2 . The structure and morphology of the samples were studied by TEM, FESEM and XRD studies. Abstract: Nanostructured ceria has been prepared in mild conditions by hydrolysis of the N, N -dibutylcarbamato complex of cerium(III), [Ce(O2 CNBu2 )3 ], obtained by lanthanide extraction from aqueous solution into heptane containing CO2 saturated NHBu2 . In dependence of the hydrolysis conditions, cerium(III) carbonates or hydroxocarbonate (characterized by IR, XRD and metal content) were obtained. Thermal treatment of these products at relatively low temperature (200 °C) yielded CeO2 in the form of a light yellow powder. The structure and morphology of the samples were studied by TEM, FESEM and XRD studies. The medium crystallite dimensions, estimated by TEM, appear to be of a few nanometers. Ceria with smaller medium crystallite dimensions was obtained by increasing the amine concentration in the course of the hydrolysis process.